Geometric and Compositional Appearance of Atheroma in an Angiographically Normal Carotid Artery in Patients with Atherosclerosis - Dong, L.; Underhill, H.R.; Yu, W.; Ota, H.; Hatsukami, T.S.; Gao, T.L.; Zhang, Z.; Oikawa, M.; Zhao, X.; Yuan, C. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Arterial remodeling may enable atherosclerotic disease without luminal stenosis. We sought to assess the prevalence and characteristics of atherosclerosis in angiographically normal carotid arteries. MATERIALS AND METHODS: Forty-six arteries with 0% stenosis by MRA were evaluated with multicontrast carotid MR imaging at 3T. For each artery, the percentage wall volume (wall volume/[lumen volume + wall volume] × 100%) and the presence versus absence of an LRNC, calcification, IPH, and fibrous cap rupture were recorded. In addition, the relative size of each plaque component (eg, percentage LRNC = LRNC volume/wall volume × 100%), when present, was calculated. RESULTS: The mean of percentage wall volume in arteries with 0% stenosis was 43.0 ± 6.9% with a range from 31.6% to 60.1%. An LRNC was present in 67.4% (31/46) of arteries, calcification was present in 65.2% (30/46), IPH was present in 8.7% (4/46), and fibrous cap rupture was present in 4.3% (2/46). In arteries with an LRNC (n = 31), the average percentage LRNC volume was 8.8 ± 7.3% with a range from 1.0% to 31.5%. For calcification (n = 30), the mean percentage calcification volume was 3.8 ± 4.2% with a range of 0.1%–17.4%. The mean percentage IPH volume (n = 4) was 2.7 ± 1.7% with a range of 0.5%–4.1%. CONCLUSIONS: These findings indicate that stenosis by MRA may underestimate the presence of carotid atherosclerosis, and they demonstrate the need for improved methods for accurately identifying carotid atherosclerotic plaque severity. CBcarotid bulbCCAcommon carotid arteryCEcontrast-enhancedECSTEuropean Carotid Surgery TrialETLecho-train lengthHDLhigh-density lipoproteinICAinternal carotid arteryImQimage qualityIPHintraplaque hemorrhageLDLlow-density lipoproteinLRNClipid-rich necrotic coreMIPmaximum intensity projectionMRAMR angiographyNASCETNorth American Symptomatic Carotid Endarterectomy TrialPDWproton-attenuation weightedSIsignal intensityT2WT2-weightedTOFtime-of-flight.